(untitled) (Journal of the College of Basic Education, 2024)
The discipline of Sociolinguistics is a vast one in which there are many fascinating topics of research that can give an excitement to scholars who are interested in knowing more about the riddles of the languages of the world. One of these topics is the topic of language and regional variation. If one looks at different parts of the world, he will find that there are many people who have different and various kinds of languages and these languages will have different variations whether socially or regionally. Also, it can be seen that the same language that can be found in one country will be influenced in its vocabulary, grammar and pronunciation by the speakers who live in different regions that belong to the country in which this language is found. This topic is one in the discipline of Sociolinguistics that can reveal many interesting facts about the same language which is spoken differently depending on the regions of the country. As a result, this study tries to provide a brief discussion to show some information about the topic of language and regional variation to the Iraqi EFL college instructors and to clarify to them the importance of considering the topic of regional variations of the English language that they are trying to teach to their students.